2012
DOI: 10.1007/s00359-012-0726-1
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone dynamics during encounter: role of emotional factors

Abstract: This study attempts to develop a new theory to explain the varying dynamics of testosterone levels in dominant (winners) and subordinate (losers) males, both pre- and post-encounter. The crux of our new theory consists of the following four theses: (1) the strengthening of testosterone synthesis is a result of not only the existence of challenges, but also of a positive mood before an encounter that is associated with the anticipation of a victory; (2) in situations where the anticipation of victory is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 117 publications
4
13
0
Order By: Relevance
“…As previously reported (Allison et al, 2012;Meyer et al, 2015), participants in the current study reported positive emotions and showed ANS activation consistent with experiencing an enjoyable rush during skydiving. The current data also show that this pleasurable activity was associated with increased testosterone reactivity consistent with suggestions that testosterone release is pleasurable (Chichinadze, Lazarashvili, Chichinadze, & Gachechiladze, 2012) and observations of testosterone increases in contexts that are exciting (e.g., sex; Escasa, Casey, & Gray, 2011;Hirschenhauser, Frigerio, Grammer, & Magnusson, 2002). Physical, visceral sensations play an important role in decision-making (Paulus, 2007).…”
Section: Sensation Seeking Stress Biomarkers and Testosteronesupporting
confidence: 88%
“…As previously reported (Allison et al, 2012;Meyer et al, 2015), participants in the current study reported positive emotions and showed ANS activation consistent with experiencing an enjoyable rush during skydiving. The current data also show that this pleasurable activity was associated with increased testosterone reactivity consistent with suggestions that testosterone release is pleasurable (Chichinadze, Lazarashvili, Chichinadze, & Gachechiladze, 2012) and observations of testosterone increases in contexts that are exciting (e.g., sex; Escasa, Casey, & Gray, 2011;Hirschenhauser, Frigerio, Grammer, & Magnusson, 2002). Physical, visceral sensations play an important role in decision-making (Paulus, 2007).…”
Section: Sensation Seeking Stress Biomarkers and Testosteronesupporting
confidence: 88%
“…Pressing the spin button on a slot machine may not be sufficient to provoke these experiences. As mentioned previously, McCaul, Gladue, and Joppa (1992) Chichinadze, Lazarashvili, Chichinadze, & Gachechiladze, 2012;Salvador & Costa, 2009) following the slot machine session was naturally higher in winners than losers, and indirectly mediated a decrease in testosterone. Because this mediational effect of Positive Affect was specific to winners, these results suggest that winners experienced a reverse winner-loser effect.…”
Section: Slot Machine Gambling: Evidence For a Winner-loser Effect?supporting
confidence: 52%
“…For example following a change in social status like winning a Tetris tournament, basal HPG-axis production of testosterone predicts cortisol reactivity for both sexes (Mehta et al, 2008) and viceversa among men (Zilioli and Watson, 2012). Moreover, enhanced testosterone production in the context of competition can amplify assertiveness and aggression when social status is threatened (Chichinadze et al, 2012a;Chichinadze et al, 2012b). As this is highly likely in the context of the TSST, studying repeated measurement of HPG-axis and HPA-axis products represents an exciting lens from which to further understand within-sex variations in stress physiology that go beyond binary sex differences.…”
Section: Discussionmentioning
confidence: 99%